Nomogram-based risk stratification to analyze the value of receiving postoperative adjuvant therapy after neoadjuvant immunochemotherapy for patients with locally advanced esophageal squamous carcinoma - An, Qiuying; Wang, Hongyan; Zhu, Hui; Jia, Yage; Liu, Yibing; Liu, Zheng; Yan, Jin; Zhang, Zihan; Wang, Yajing; Zhang, Ping; Zhou, Zhiguo (Frontiers in Immunology, 2025)
PurposeTo develop a prognosis nomogram for locally advanced esophageal squamous cell carcinoma (LA-ESCC) patients after neoadjuvant immunochemotherapy (NICT) and assess postoperative adjuvant therapy (PAT) value through survival risk stratification.MethodsWe retrospectively analyzed 297 LA-ESCC patients (2019–2023) receiving NICT with or without PAT, randomly divided into the training and validation cohorts. Independent prognostic factors were determined by Least Absolute Shrinkage and Selection Operator (Lasso) regression and multivariate Cox analysis. Progression-free survival (PFS) was compared by the Kaplan-Meier analysis.ResultsThe median follow-up time after surgery was 31.67 months (2.23-62.5 months) as of January 25, 2025. The 1-year and 2-year PFS rates were 82.8% and 67.8%. The analysis identified tumor length, tumor thickness reduction rate, surgical method, number of lymph nodes dissected, and ypN-stage as independent prognostic factors. In the training and validation cohorts, the Concordance Index (C-index) of the nomogram was 0.776 and 0.818. The area under the curve (AUC) values for predicting 1-year PFS were 0.823 and 0.899, while the AUC values for predicting 2-year PFS were 0.802 and 0.810, respectively. According to the nomogram, patients were divided into three risk groups (low, medium, and high), and there were significant differences in PFS among the groups (P<0.001). Survival analysis showed that PAT significantly improved PFS in the high-risk group (1-year: 53.3% vs. 26.7%; 2-year: 35.6% vs. 6.7%, P=0.009), but there was no significant difference in the low and medium risk groups.ConclusionThe prognosis nomogram can effectively predict the PFS of LA-ESCC patients after NICT. Through survival risk stratification, patients in the high-risk group may benefit from PAT.